White Hot - Sandra Brown 1948- (New York Pocket Books, Inc., 2005)
Returning to her Louisiana hometown after the suicide of her younger brother, Danny, Sayre Lynch examines the turbulent relationship between Danny and their favored older brother and begins to suspect that Danny was murdered.
Keywords: Literature (3GdCOHs; General -- Death -- Fiction; Brothers; Conflict of generations -- Fiction; Iron industry and trade -- Fiction; Family-owned business enterprises -- Fiction